2008
DOI: 10.1210/er.2008-0017
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of Energy Homeostasis by the Estrogen-Related Receptors

Abstract: Transcriptional control of cellular energy metabolic pathways is achieved by the coordinated action of numerous transcription factors and associated coregulators. Several members of the nuclear receptor superfamily have been shown to play important roles in this process because they can translate hormonal, nutrient, and metabolite signals into specific gene expression networks to satisfy energy demands in response to distinct physiological cues. Estrogen-related receptor (ERR) alpha, ERRbeta, and ERRgamma are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
474
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(488 citation statements)
references
References 165 publications
6
474
0
1
Order By: Relevance
“…In immunity, ERRα −/− mice exhibit increased susceptibility to Listeria monocytogenes infection (23). Although not previously investigated in lymphocytes, these findings suggest ERRα may regulate genes that contribute to lymphocyte metabolism and activation (20,21).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In immunity, ERRα −/− mice exhibit increased susceptibility to Listeria monocytogenes infection (23). Although not previously investigated in lymphocytes, these findings suggest ERRα may regulate genes that contribute to lymphocyte metabolism and activation (20,21).…”
mentioning
confidence: 77%
“…The orphan nuclear hormone receptor, estrogen-related receptor-α (ERRα), is associated with poor prognosis (16,17) and tumor growth in breast cancer (18,19). ERRα is also known to regulate cell metabolism (20,21) and Drosophila ERR can promote gene expression to drive carbohydrate metabolism associated with proliferating cells in larval development (22). In immunity, ERRα −/− mice exhibit increased susceptibility to Listeria monocytogenes infection (23).…”
mentioning
confidence: 99%
“…37 We showed that NPY deficiency per se significantly increased brown adipose tissue weight, with no significant effect of OVX in mice of either genotype ( Figure 2a). There was no significant effect of OVX on UCP-1 or PGC1a (c) Dual-energy X-ray absorptiometry (DXA) scans at 18 and 54 days post surgery, referred to as 'short-term' and 'long-term' time-points, respectively, reveal that OVX-induced increases in whole-body fat mass in both genotypes occur only after long-term estrogen deficiency, with NPY À / À mice exhibiting a reduction in fat mass after short-term estrogen deficiency.…”
Section: Effectmentioning
confidence: 88%
“…Therefore, the two nuclear receptors seem to regulate most glycolytic genes by binding to the same genetic loci. However, considering that Ad4BP/SF-1 is expressed only in endocrine tissues, for example, the adrenal cortex and gonads 3,10 , whereas ERRa is expressed in a broad range of tissues 48 , the contribution of these two nuclear receptors to glycolytic gene regulation likely varies among tissues.…”
Section: Discussionmentioning
confidence: 99%